AN OVERVIEW OF CRITICAL READING STRATEGIES TO EFL STUDENTS - Rosdiana (English Education Department, 2015)
This article describes about Critical Reading Strategy in teaching English, especially in reading comprehension. Critical Reading is a strategy that provides students with instructional support before, during, and after reading process. The students with critical reading skills have the ability to evaluate the credibility of a piece of writing. All writers have a purpose when they write, and usually a writer will choose or emphasize facts and details which support his or her purpose, and ignore facts which don't. As readers make sense of what they read, they use various relationships of ideas to aid recognition and fluency. Critical reading includes the ability to evaluate ideas and synthesize what one reads. They are the ability to see relationships of ideas and use them as an aid in reading.